(untitled) (Journal of history, 2018)
The article vefleets, the main directions of the housing policy of the Soviet state in the industrial city of Kentau in 1955-1991. The dynamics of housing construction in this period is analyzed, the level of providing the population with living space, the quality and condition of the housing itself is considered. The article is based on rich factual material extracted from archives that were not previously introduced into scientific circulation. At all stages of the historical development of human civilization, the housing problem was one of the most important: to have a dwelling-the basic need of homo sapiens. But the solution of this problem in different countries and among different peoples was carried out and is carried out on the basis of different approaches and with different levels of complexity. In the Soviet and post-Soviet periods, from year to year, the volume of housing construction increased, and the lack of housing, however, became chronic.